The development of the Auckland Primary Principals' Association 1901-1998 : a study of a voluntary, professional organisation in the New Zealand education system : a thesis presented in partial fulfillment of the requirements for the degree of Master in Education at Massey University, - Langston, Nigel (Massey University, 1999)
This study investigates how, and why, over a period of approximately 97 years, primary principals developed the Auckland Primary Principals' Association (APPA) along particular lines. Hereafter, this discussion will refer to it as the Association or the APPA. The two central questions addressed are how the organisation served the needs of particular groups and how it served the needs of primary education in New Zealand. Supporting these two questions are four areas of focus - the extent of change, the external and/or internal catalysts, the political role of the Association and the Association's adaptation to the times. The Auckland Headmasters' Association (AHMA), now called the APPA, as an education organisation, was, and remains, a middle level organisation. It operated as a conduit between grass-roots concerns of classroom teachers and more embracing organisations such as the Department of Education and the Auckland Education Board (AEB). It provided a special forum, initially for Auckland headmasters and later for Auckland primary principals. It has been shown that the commonly held dual membership of the AHMA and New Zealand Educational Institute (NZEI) was usually a happy relationship. The AHMA acted as a male pressure group supporting policies that were beneficial to male principals and male senior teachers. By creating a separate organisation, the APPA, in its political role, had the choice of direct access to the Minister of Education, and proposals could also be made through the NZEI or, to a lesser extent, the Education Boards Association. This is an organisation not touched on directly by other New Zealand educational histories. Of central importance to the thesis is an account of how the AHMA/APPA acted as a pressure group, funnelling grievances, modifying them, negotiating with the education administration above it and also accommodating itself to the demands of those below it. Also, when describing the activities of the Association, a clear picture emerges of a non-controversial negotiating style. Both traditional literary, historical techniques and oral history methods were used in gathering data and in interpreting them.
Keywords: Elementary school principals -- New Zealand; Auckland; Northland; Auckland Primary Principals' Association; History